STRUCTURING OF THE PERSPECTIVE NAVIGATION-LANDING ONBOARD COMPLEX AIRCRAFTS OF THE SUBURBAN SIZES - Kondrashov, Ya.; Fialkina, T.; Khomenko, D. (Science-based technologies, 2011)
In article considers the concept formation of airborne navigation and landing of aircraft complex local airlines, identified its components and their interconnections.